2016
DOI: 10.1016/j.matlet.2016.04.178
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast cell response to oxide films formed on nanograin 316L stainless steel obtained by two-dimensional linear plane-strain machining

Abstract: a b s t r a c tThe long-term success of orthopedic implants is strongly determined by their surface characteristics and the interaction of this surface with the surrounding biological environment. The biocompatibility of metallic biomaterials is mainly due to their ability to form an adherent oxide layer on their surface that is in direct contact with the biological environment. In this study, oxide layers were grown on ultra-fine grained 316L stainless steel samples, naturally, chemically and thermally. Sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…12 Cell cytotoxicity was assessed by a colorimetric assay using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT, CT02 MTT Cell Growth Assay Kit, EMD Millipore, Darmstadt, Germany). 13 After 48 hours incubation time, 0.01 ml pre-warmed MTT solution was added to each culture well containing 0.1 ml fresh cell medium and the cell culture plate containing MTT solution continued incubation for 4 hrs under the same conditions. MTT solution has a pale yellow color which live cells cleave it to yield a dark blue formazan product.…”
Section: Biocompatibility Evaluation Using Endothelial Cell Adhesion Testmentioning
confidence: 99%
“…12 Cell cytotoxicity was assessed by a colorimetric assay using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT, CT02 MTT Cell Growth Assay Kit, EMD Millipore, Darmstadt, Germany). 13 After 48 hours incubation time, 0.01 ml pre-warmed MTT solution was added to each culture well containing 0.1 ml fresh cell medium and the cell culture plate containing MTT solution continued incubation for 4 hrs under the same conditions. MTT solution has a pale yellow color which live cells cleave it to yield a dark blue formazan product.…”
Section: Biocompatibility Evaluation Using Endothelial Cell Adhesion Testmentioning
confidence: 99%
“…The great advantage of porous layers produced by micro-arc oxidation is the enhanced corrosion resistance [ 50 , 51 , 52 , 53 ], which is an important aspect in the selection of components used for medicine and other industries. Unfortunately, there is little literature on porous layers’ characteristics on stainless steel produced by the micro-arc oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in terms of biomedical applications, Asoh et al [29] reported the growth of anodic layers on type 304 stainless steel in an anodizing bath of hydrogen peroxide and sulfuric acid is suitable to prepare the surface prior to the deposit of synthetic bioactive hydroxyapatite in biomedical implant devices. However, even though corrosion resistance is an important issue in medical devices and applications [32,33], literature is scarce in the electrochemical characterization of anodic layers on stainless steel.…”
Section: Introductionmentioning
confidence: 99%